Analysis of Trip Attraction in Shopping Centres Suzaya Mall Bireuen based on demographic characteristic - Usrina, Nura; M. Fauzan; Lis Ayu Widari; Syibral Malasyi; Raihan Fazila (Edusight International Journal of Multidisciplinary Studies, 2025)
Trip attraction refers to the number of trip movements toward a specific location per unit of time. This concept is directly related to determining the total trips generated by particular land uses. The establishment of Suzuya Mall by the government has significantly increased private and public vehicle traffic in Bireuen City, leading to frequent road congestion. During peak movement periods, vehicles often stop or park along the road near Suzuya Mall, reducing overall road capacity. This study examines three key aspects: the characteristics of visitors to Suzuya Mall, the factors influencing trip attraction in this land use area, and the development of a trip attraction model for Suzuya Mall in Bireuen City. The research methodology incorporated questionnaire data collection and SPSS-based data processing. Analysis was conducted using multiple linear regression through SPSS 25 software, with model validation assessed through multicollinearity values, correlation coefficients (R), determination coefficients (R²), heteroscedasticity tests, significance values, and P-P plot graphs. The study yielded a comprehensive trip attraction model for all vehicle types: Y = 61.157 + 0.123(X₁) + 2.75(X₂) - 0.716(X₃) + 0.195(X₅), where X₁ represents age, X₂ denotes income, X₃ indicates distance, and X₅ reflects mileage. The model achieved a determination coefficient value of 0.964, demonstrating strong explanatory power for trip attraction patterns in the Suzuya Mall area.